Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Pasien Klinik Kasih Bunda Medika Leuwinanggung - Widia Sari, Annisa; Elmira Siska; Natal Indra (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to analyze the effect of service quality and facilities on patient satisfaction at Kasih Bunda Medika Clinic. The research approach used in this study is quantitative statistics by collecting primary data through questionnaires. The sample of this study were 50 patients who were treated at the Kasih Bunda Medika Clinic using an accidental sampling technique. Data analysis used descriptive statistical techniques. SPSS Statistics 25 software was used to test data statistics, multiple regression analysis, and hypothesis testing. The results showed that partially, service quality had a positive and not statistically significant effect on patient satisfaction, while service facilities showed a positive and statistically significant effect on patient satisfaction. patient. Simultaneously, it shows that the quality of services and facilities has a positive and significant effect on patient satisfaction.